Excitation functions of the proton induced nuclear reactions on natural zirconium - Khandaker, Mayeen Uddin; Kim, G.N.; Uddin, M.S.; Kim, K.S.; Lee, M.W.; Lee, Y.S. (Elsevier, 2008)
Excitation functions for the Zr-nat(p,xn)Nb-90,Nb-92m,Nb-95g,Nb-96,Zr-nat(p,pxn)Zr-88,Zr-89, and Zr-nat(p,alpha xn)Y-86,Y-87m,Y-87mg,Y-88 reactions were measured by using a stacked-foil activation technique in combination with HPG gamma-ray spectroscopy using the MC50 cyclotron at the Korean Institute of Radiological and Medical Sciences, Korea. In this way the proton beam energy range 4-40 MeV was covered. We report new data for these processes. The data were compared with the results of precompound-hybrid model calculations, whereby only a partial agreement was obtained. (C) 2007 Elsevier B.V. All rights reserved.